Export Expansion May Increase Adult Illness and Injury: A Quasi-Natural Experiment on China's Accession to the World Trade Organization - Hongwen Chen; Junbing Xu; Jianzheng Liu (Frontiers Media S.A., 2022)
PurposeExports can boost the economy, but may also cause harm to health through, for example, increased pollution and working hours. Although academic research extensively covers the impact of trade on health, few studies examine the mechanisms through which export expansion affects adult illness or injury within the past 4 weeks (illness/injury).MethodWe utilized China's entry into the World Trade Organization (WTO) as a quasi-natural experiment to investigate the relationship between export expansion and adult illness/injury. We explored the possible mechanisms and the heterogeneity of these associations. Our methodology was based on the analysis of China's Health and Nutrition Survey data, Chinese Customs databases, and China's Statistical Yearbook.ResultsExport expansion, induced by China's accession to the WTO, has a significantly positive effect on adult illness/injury [average effect (AE): 1.83%; 95% CI: 0.38-3.28%]. Our results remain robust following a series of robustness tests. Moreover, the effects of export expansion on adult illness/injury are more pronounced among urban residents (AE: 5.32%; 95% CI: 2.46-8.18%), women (AE: 2.68%; 95% CI: 0.57-4.80%), and higher-income groups (AE: 5.90%; 95% CI: 2.53-9.27%).ConclusionsWe find a statistically significant and positive effect of export expansion on adult illness/injury.